Selection and Clonal Propagation of Leucaena Leucocephala(LAM.) De Wit. for Biomass Production on Substandard Soil Sites - Gautam, N. N.; Singh, Kripal; Singh, Bajrang; Goel, V. L.; Rahi, T. S. (Indian Forester, 2012)
The study was a part of biomass research programme on selection and improvement of fast growing leguminous tree species suitable for short rotation bio-energy plantations on sodic soil sites (pH 8.6 to 10.5). It included selection of promising seed sources and plus trees followed by cloning of selected coppiced trees in Leucaena leucocephala (K8 variety) for high biomass productivity on sodic soils. Evaluation of field performance of five seed sources revealed best performance of plants in Madurai seed source after 3-year of growth while plants of Oxford seed source showed poor performance as compared to plants of other seed sources investigated during present study. Intra-specific variations were observed at individual tree level in an even aged 8-yr-old population. Several plus trees (30) were identified on the basis of phenotypic superiority in plant height, trunk thickness and biomass productivity. Successful populations (gene pools) and individual plus trees were multiplied vegetatively using coppice shoots and conserved as a future resource for production of site adapted quality germplasm for plantations on sodic wastelands. The study would help in establishing site adapted germplasm for optimizing gains in future afforestation programmes on degraded forest and community lands.